ChemInform Abstract: Metal‐Free Direct Nucleophilic Perfluoroalkylthiolation with Perfluoroalkanesulfenamides. Issue 30 (7th July 2016) - Glenadel, Quentin; Bordy, Mathieu; Alazet, Sebastien; Tlili, Anis; Billard, Thierry
Abstract: Anions generated in situ from perfluoroalkanesulfenamides undergo direct metal‐free nucleophilic substitution reactions with a wide range of alkyl halides to form the corresponding products.